Factors Predicting Ventilator Dependence in Patients with Ventilator-Associated Pneumonia - Chia-Cheng Tseng; Kuo-Tung Huang; Yung-Che Chen; Chin-Chou Wang; Shih-Feng Liu; Mei-Lien Tu; Yu-Hsiu Chung; Wen-Feng Fang; Meng-Chih Lin (The Scientific World Journal)
Objectives. To determine risk factors associated with ventilator dependence in patients with ventilator-associated pneumonia (VAP). Study Design. A retrospective study was conducted at Chang Gung Memorial Hospital, Kaohsiung, from January 1, 2007 to January 31, 2008. Methods. This study evaluated 163 adult patients (aged ≥18 years). Eligibility was evaluated according to the criterion for VAP, Sequential Organ Failure Assessment (SOFA) score, Acute Physiological Assessment and Chronic Health Evaluation II (APACHE II) score. Oxygenation index, underlying comorbidities, septic shock status, previous tracheostomy status, and factors related to pneumonia were collected for analysis. Results. Of the 163 VAP patients in the study, 90 patients survived, yielding a mortality rate of 44.8%. Among the 90 surviving patients, only 36 (40%) had been weaned off ventilators at the time of discharge. Multivariate logistic regression analysis was used to identify underlying factors such as congestive cardiac failure (P=0.009), initial high oxygenation index value (P=0.04), increased SOFA scores (P=0.01), and increased APACHE II scores (P=0.02) as independent predictors of ventilator dependence. Results from the Kaplan-Meier method indicate that initial therapy with antibiotics could increase the ventilator weaning rate (log Rank test, P<0.001). Conclusions. Preexisting cardiopulmonary function, high APACHE II and SOFA scores, and high oxygenation index were the strongest predictors of ventilator dependence. Initial empiric antibiotic treatment can improve ventilator weaning rates at the time of discharge.